26.3k views
3 votes
What is the simplified form of the following expression?

What is the simplified form of the following expression?-example-1
User Malcooke
by
5.0k points

1 Answer

2 votes

For this case, we must simplify the following expression:


2 \sqrt {27} + \sqrt {12} -3 \sqrt {3} -2 \sqrt {12}

Then, rewriting terms:


2 \sqrt {27} = 2 \sqrt {9 * 3} = 2 \sqrt {3 ^ 2 * 3} = 6 \sqrt {3}\\\sqrt {12} = \sqrt {3 * 4} = \sqrt {2 ^ 2 * 3} = 2 \sqrt {3}\\2 \sqrt {12} = 2 \sqrt {3 * 4} = 2 \sqrt {2 ^ 2 * 3} = 4 \sqrt {3}

Rewriting the expression:


6 \sqrt {3} +2 \sqrt {3} -3 \sqrt {3} -4 \sqrt {3} = \sqrt {3}

Answer:


\sqrt {3}


User HariKarthick
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.